2018
DOI: 10.3892/mmr.2018.8619
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous adipogenic differentiation potential of adipose‑derived stem cells decreased with increasing cell passages

Abstract: Primary adipose-derived stem cells (ADSCs) are a mixture of cell types including preadipocytes having the ability to spontaneously differentiate into adipocytes. The aim of the present study was to compare the spontaneous adipogenic differentiation potential of ADSCs at different passages to determine whether it decreased with continuous cell passages. Mouse ADSCs (mADSCs) were harvested and cells from passages 1 to 5 were used for experiments. The proliferation of mADSCs at different passages was tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…After 4 weeks of culture, hASCs cultured in differentiation media accumulated intracellular lipid droplets with a mixture of multilocular and unilocular cells ( Figure 3 C), while the slices cultured in growth media showed minimal differentiation ( Figure 3 B). Not surprisingly, the growth media promoted a small amount of spontaneous lipid accumulation, which we attribute to the low passage number of the hASCs used [ 45 ] and the high confluence [ 46 , 47 ]. Metabolic activity was also assessed in the tissue slices at the end of week 1 and week 4 ( Figure 3 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…After 4 weeks of culture, hASCs cultured in differentiation media accumulated intracellular lipid droplets with a mixture of multilocular and unilocular cells ( Figure 3 C), while the slices cultured in growth media showed minimal differentiation ( Figure 3 B). Not surprisingly, the growth media promoted a small amount of spontaneous lipid accumulation, which we attribute to the low passage number of the hASCs used [ 45 ] and the high confluence [ 46 , 47 ]. Metabolic activity was also assessed in the tissue slices at the end of week 1 and week 4 ( Figure 3 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the undifferentiated state of ADSCs in the cell sheet was confirmed by the positive expression of CD105 and CD44 surface markers, as well as intracellular vimentin. Some studies revealed that ADSCs could differentiate into adipogenic [ 50 ], osteogenic, and chondrogenic lineages [ 51 ] after adding ascorbic acid [ 52 ] and long-term culturing [ 53 , 54 ], which has the risk of unwanted tissue formation. Hence, the undifferentiated state of ADSCs in cell sheets was confirmed using oil red O, Alizarin red, and Alcian blue staining following 10 days of culture with ascorbic acid or induction medium.…”
Section: Discussionmentioning
confidence: 99%
“…After 4 weeks, hASCs cultured in differentiation media accumulated intracellular lipid droplets with a mixture of multilocular and unilocular cells (Figure 3 C), while the slices cultured in growth media showed minimal differentiation (Figure 3 B). Not surprisingly, the growth media promoted a small amount of spontaneous lipid accumulation, which we attribute to the low passage number of the hASCs used [47] and the high confluence [48, 49]. Metabolic activity was also assessed in the tissue slices at the end of week 1 and week 4 (Figure 3 D-E).…”
Section: Resultsmentioning
confidence: 99%